2014
DOI: 10.1007/s00520-014-2418-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle mass on toxicity and survival in patients with colon cancer undergoing adjuvant chemotherapy

Abstract: Decreased muscle mass was associated with increased risk of grade 3-4 toxicity and poor prognosis in patients with stage III colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
179
4
14

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(200 citation statements)
references
References 39 publications
3
179
4
14
Order By: Relevance
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
“…PA has shown a correlation with post‐operative complications in individual studies on colorectal cancer, colorectal liver metastases, kidney cancer, bladder cancer, cholangiocarcinoma, and hepatocellular cancer,11, 12, 13, 14, 15, 16 while this effect was not seen in other pancreatic cancer, endometrial cancer, biliary cancer, or sarcoma studies 17, 18, 19, 20. Interestingly, only few cancer studies were able to show a correlation between PA and survival 21, 22, 23. In a small number of non‐cancer studies, decreased psoas muscle area has also been correlated with higher rates of morbidity24, 25, 26 and mortality25, 27, 28, 29 in patients undergoing cardiothoracic, gastro‐intestinal, and spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, adjuvant chemotherapy was avoided for patients with sarcopenic condition at each physician's judgment. Sarcopenia is reportedly associated with increased risk of toxicity in patients with colon cancer who undergo adjuvant chemotherapy (17). If patients who will get benefit from adjuvant chemotherapy can be selected, a prognosis of patients with sarcopenia may improve.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, muscle wasting and low muscle mass have been linked to poorer survival and increased risk of treatment toxicity in various cancer diagnoses, including NSCLC 15, 16, 17, 18, 19. In advanced NSCLC, a recent study from our group showed that low muscle mass was a significant predictor for chemotherapy‐induced haematological toxicity 20…”
Section: Introductionmentioning
confidence: 99%